An Economic Analysis of Funding and Enrolment in Nigerian Universities: 1970- 2003 - Akanbi, Bosede Esther (2015)
The study examined the relationship between funding and enrolment in Nigerian universities between 1970 and 2003. It also analysed the trends and patterns of funding and enrolments in Nigerian universities and the causality between them. These were done with the aim of drawing out the implications of the findings for effective planning on university enrolment.